2020
DOI: 10.3390/molecules25020271
|View full text |Cite
|
Sign up to set email alerts
|

The Underlying Mechanisms of Curcumin Inhibition of Hyperglycemia and Hyperlipidemia in Rats Fed a High-Fat Diet Combined With STZ Treatment

Abstract: Curcumin is the main secondary metabolite of Curcuma longa and other Curcuma spp, and has been reported to have some potential in preventing and treating some physiological disorders. This study investigated the effect of curcumin in inhibiting high-fat diet and streptozotocin (STZ)-induced hyperglycemia and hyperlipidemia in rats. Twenty-six male Sprague-Dawley (SD) rats (170–190 g) were randomly divided into a standard food pellet diet group (Control group), a high-fat diet and streptozotocin group (HF + STZ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 56 publications
(64 reference statements)
2
21
0
Order By: Relevance
“…The present study recorded a significant elevation in the weight of the HFD-fed animals comparing with the control group that may be due to the deposition of fats in various body fat pads. This finding is consistent with the results obtained by Xia et al [16] in the HFD-fed diabetic rat. Additionally, Fidèle et al [17] found that the cholesterol accumulation caused an increase in the rate of steroid hormone production such as cortisol, estrogens, and testosterone leading to an increase in the body weight of HFD-fed rats.…”
Section: Discussionsupporting
confidence: 94%
“…The present study recorded a significant elevation in the weight of the HFD-fed animals comparing with the control group that may be due to the deposition of fats in various body fat pads. This finding is consistent with the results obtained by Xia et al [16] in the HFD-fed diabetic rat. Additionally, Fidèle et al [17] found that the cholesterol accumulation caused an increase in the rate of steroid hormone production such as cortisol, estrogens, and testosterone leading to an increase in the body weight of HFD-fed rats.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, the liver is generally known to be the central regulator of lipid homoeostasis. Many studies have shown that elevated levels of plasma free fatty acids in DM patients stimulate the liver to synthesize and secret large amounts of TG and LDL [28][29][30]. In our present study, we found that the levels of TC, TG, LDL, and HDL were abnormal in STZ-induced diabetic rats.…”
Section: Discussionsupporting
confidence: 56%
“…Insulin deficiency causes metabolic disorders and the accumulation of harmful substances in the liver leading to severe oxidative stress [27]. STZ treatment to rats leads to liver biochemical disorders, which is manifested by the abnormal expression of active substances, such as ALT and AST [28]. The results of this study clearly showed the high level of ALT and AST serums in STZ-induced immature diabetic rats.…”
Section: Discussionmentioning
confidence: 56%
“…The treated groups maintained a higher plasma glucose than the CK group at the end of 120 min. This finding suggested that the plasma glucose in the treated mice spent more time restoring to normal, indicating that pesticide exposure lowered the capacity of the body to regulate glucose [ 11 ].…”
Section: Resultsmentioning
confidence: 99%